2005
DOI: 10.1103/physrevlett.95.077203
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Distortion Effects on the Magnetostructural Phase Transition of MnAs

Abstract: We present a systematic experimental and theoretical study of the first-order phase transition of epitaxially grown MnAs thin films under biaxial tensile stress. Our results give direct information on the dependence of the phase-transition temperature of MnAs films on the lattice parameters. We demonstrate that an increase of the lattice constant in the hexagonal plane raises the phase-transition temperature (T p ), while an increase of the perpendicular lattice constant lowers T p . The results of calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
(28 reference statements)
5
24
1
Order By: Relevance
“…The results for K a and K b differ slightly from the ones given in Ref. 8, since in that case we did not constrain K a to be equal to K b . If the cell changes only its volume, the expansion corresponds to the one of Eq.…”
Section: B31 To B8 1 Distortion At T Tcontrasting
confidence: 88%
See 1 more Smart Citation
“…The results for K a and K b differ slightly from the ones given in Ref. 8, since in that case we did not constrain K a to be equal to K b . If the cell changes only its volume, the expansion corresponds to the one of Eq.…”
Section: B31 To B8 1 Distortion At T Tcontrasting
confidence: 88%
“…This is mainly attributed to the induced strain. 1,3,7,8 The aim of this paper is to use ab initio density functional theory ͑DFT͒ calculations to develop an understanding of the phase transitions of MnAs, which can be compared with experiments and with existing phenomenological models.…”
Section: Introductionmentioning
confidence: 99%
“…MnAs, which is a ferromagnetic metal at room temperature, is on the focus of attention because it can be successfully integrated with semiconductors such as GaAs [1], Si [2] and ZnSe [3]. Several magnetic and structural characterizations as a function of temperature have been done on MnAs [4][5][6], but the magneto-electrical transport properties remain still unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…Kaganer et al [11] have shown that the epitaxial strain leads to the α − β phase coexistence to minimize the elastic energy. Strain dependent magnetic properties were analyzed by Das et al [12] and Iikawa et al [13] in the case of MnAs epitaxied on GaAs(001). The unit cell of the ferromagnetic α-phase was found to be orthorhombically distorted, as the hexagonal plane of MnAs lies out of the substrate surface.…”
mentioning
confidence: 99%
“…We anticipate that larger T (2) C critical temperature may be obtained by increasing the tensile strain in the film plane. This could be achieved by applying external strain to the substrate similarly to the experiments performed by Iikawa et al [13]. For example, if we apply a tensile strain of 0.5% in the film plane, it would be possible to increase the critical temperature to T (2) C =373 K [19].…”
mentioning
confidence: 99%